A Conversational Implicature Analysis of Joko Widodo’s English Speech - Ratih Asti Supriyanto (La Tansa Mashiro, 2020)
This study aimed to find out the implicature that produce by Joko Widodo in his English first speech as a president of Indonesia. The approach that used in this study is qualitative research involving descriptive method which analyse Joko Widodo’s speech. The finding of this study showed that Joko Widodo’s speech have domination in generalized conversational implicature which inferred without a special reference to context, and particularized conversational implicatures that produced by Joko Widodo in his English speech only 21% from whole of the speech.